Analysis of the potential impact of capillarity on long-term geochemical processes in sulphidic waste-rock dumps. (November 2015) - Pedretti, Daniele; Lassin, Arnault; Beckie, Roger D.
Highlights: Capillarity may affect geochemical reactions generating acid-rock drainage. We studied its impact in a simplified, synthetic WRD. Capillarity mainly affects the formation of secondary minerals. It can strongly control long-term formation of gypsum and in turn sulfate release. Capillarity can be also important for the analysis of calcite passivation. Abstract: Assessing long-term production of acid rock drainage (ARD) from waste-rock dumps (WRDs) requires a careful analysis of the processes controlling acid-generating geochemical reactions under unsaturated conditions. In this work, we focus on the potential control of capillarity on these reactions, as previous studies showed that capillarity affects the activity of water and solutes in the unsaturated zone through the pore water pressure. We used capillarity-corrected thermodynamic databases and compared calculated speciation and solubility results with those from databases that do not account for capillarity. We developed a simple dynamic model with reduced geochemical components to analyze in detail the effect of capillarity. Results indicate that under low pH conditions simulations with capillarity-controlled reactions generate relatively larger dissolved sulfate concentrations from the WRDs over longer time scales, when compared against simulations without capillarity control. This occurs because capillarity strongly controls the formation of secondary sulfate-bearing minerals such as gypsum. When sufficient oxygen and carbon dioxide partial pressures are maintained within WRDs (such as in well-ventilated systems) and calcite content is insufficient to buffer acidity, the amount of secondary gypsum was calculated to be much larger in capillarity-corrected models. No appreciable effects of capillarity were observed under conditions where gypsum was not generated. Model results are also insensitive to temperature changes in typical climatic ranges. These results indicate some of the conditions by which capillarity should be accounted for as a key component to make accurate long-term predictions concerning with ARD from WRDs, and for the correct interpretation of potential processes such as calcite passivation.